ANALISIS MOTIVASI BELAJAR PESERTA DIDIK KESULITAN BERHITUNG PERMULAAN - Derista Lidya Carolina; Nurlinda Safitri; Elly Sukmanasa (FKIP UNIVERSITAS PAKUAN, 2020)
ANALYSIS OF STUDENTS 'LEARNING MOTIVATION IN DIFFICULTY CALCULATING THE BEGINNING Difficulty in completing calculations is often experienced by students in learning. One of them is a student who has difficulty in preliminary counting such as completing addition, subtraction, multiplication and division that needs to be analyzed the motivation of these students. So that this study aims to determine the learning motivation of students who have difficulty counting at the beginning of a class VB student at SDN Genteng, Bogor City. This research was conducted using a case study qualitative research approach. In practice, the data collection and recording techniques used by researchers are triangulation of combining information between observations and interviews and documentation. This research was conducted in the Even Semester of the 2019/2020 Academic Year. The results of this study indicate that there are internal and external factors that affect the learning motivation of students who have difficulty in arithmetic. These students have the smallest number of scores during the Mid-Semester Assessment compared to their classmates. Even so, students who have difficulty counting have advantages and are uniqueness when singing. Her beautiful voice made everyone who heard it amazed. Apart from singing pop songs, these students have beautiful voices in recitations. Because these students take part in marawis activities and become vocalists.